Evaluation of Strategies for Lysing Spent Baker’s Yeast Generated Upon Production of Sago Bioethanol - Nik Nur Aziati, Mahmod (2023)
Spent Baker’s yeast (Saccharomyces cerevisiae), a by-product of the ethanol production industry, is mainly discarded as a waste. The spent yeast can be converted to yeast extract by the lysis process, in which the yeast cells are disintegrated under specific conditions to release significant bioactive components. To date, studies on the lysis strategies of spent S. cerevisiae produced after sago bioethanol synthesis is still limited. The present work was aimed to evaluate the feasibility of autolysis and enzymatic hydrolysis of spent S. cerevisiae produced following sago bioethanol fermentation. The autolysis of spent S. cerevisiae was studied according to the effect of initial pH (3, 5, and 7) and incubation time (24, 48, 72, and 96 hours). Secondly, the enzymatic hydrolysis was investigated using two different enzyme types (alcalase and cellulase) with varying enzyme doses (0.1, 0.2, 0.3, 0.4, and 0.5 %, v/v). The resulting lysates were analysed for protein and carbohydrate concentrations using Lowry assay and phenol-sulphuric acid assay, respectively. The lysed yeast cells were observed for their morphological characteristics using a scanning electron microscope. The results indicated that after 72 hours of incubation, the autolysis of spent Baker's yeast at an initial pH of 3 produced the maximum concentration of protein and carbohydrate in the autolysate. These were 2.5 and 2-fold higher than the concentrations of protein and carbohydrates in the control samples, respectively. Meanwhile, in enzymatic hydrolysis, the highest protein and carbohydrate concentration of lysate were achieved from the hydrolysis of spent Baker’s yeast using cellulase (0.5%, v/v) and alcalase (0.4%, v/v), respectively. The enhancement of protein and carbohydrate concentrations were 8.6-fold and 11.4-fold, respectively as compared to that achieved by the control experiment. The surface morphology analysis of lysed yeast cells resulting from autolysis and enzymatic hydrolysis of spent S. cerevisiae under the aforementioned conditions were parallel with the lytic events occurred during both processes. The best strategies for lysing spent Baker’s yeast generated upon production of sago bioethanol was enzymatic hydrolysis, considering to the high release of protein and carbohydrate concentration as compared to autolysis. The current work provides early insights into the potential strategies of valorising spent S. cerevisiae, generated from sago bioethanol production, where the resulting yeast extract can be used for various industrial applications.